2012
DOI: 10.1016/j.matlet.2011.10.098
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution during gaseous hydrogen charging of Zircaloy-4 processed by high-pressure torsion: A comparative study

Abstract: The original and high-pressure torsion (HPT) processed Zircaloy-4 materials were hydrided using gaseous hydrogen charging at different hydrogen pressures (10, 15 and 20 atm). The phase and microstructural evolutions of the samples during hydriding were characterized. It showed that when hydriding at the identical conditions, more hydrides tended to form in the HPT samples compared to that of the original ones. At a hydrogen pressure of 20 atm, the HPT sample was completely converted to ε-ZrH 2 while some δ-ZrH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Hydride platelets were observed to generally align along the RD direction in RD-TD planes, consistent with the results given by Kiran Kumar et al [1] and Oh et al [18] Further, it was found that a higher volume fraction of hydrides together with longer hydride platelets formed in the 20-atm-hydrided Zr-4 in contrast to that in the 10-atm-hydrided sample (Figures 3(b) and (c)). As revealed in our previous study, [19,20] a higher hydrogen absorption at the elevated hydriding pressure is yielded, favoring the growth of hydride platelets and resulting in the precipitation of a larger amount of hydrides. The Vickers microhardness values for the matrix and the hydrided samples are also shown in Figure 3(d).…”
Section: A Phase Identification and Quantificationmentioning
confidence: 56%
“…Hydride platelets were observed to generally align along the RD direction in RD-TD planes, consistent with the results given by Kiran Kumar et al [1] and Oh et al [18] Further, it was found that a higher volume fraction of hydrides together with longer hydride platelets formed in the 20-atm-hydrided Zr-4 in contrast to that in the 10-atm-hydrided sample (Figures 3(b) and (c)). As revealed in our previous study, [19,20] a higher hydrogen absorption at the elevated hydriding pressure is yielded, favoring the growth of hydride platelets and resulting in the precipitation of a larger amount of hydrides. The Vickers microhardness values for the matrix and the hydrided samples are also shown in Figure 3(d).…”
Section: A Phase Identification and Quantificationmentioning
confidence: 56%
“…Although the strength of this nanocrystalline Zr-4 material is improved, the comprehensive properties need to be evaluated before considering its practical applications in nuclear reactors, especially the resistance to hydride embrittlement. Our preliminary metallographic studies have indicated that the HPT samples exhibited the higher potential for the hydride precipitation compared with samples without HPT processing [7]. Further in-depth work concerning hydriding and its effects on structural and mechanical properties of HPT Zr-4 are essential to enhance our understanding of the hydride formation behaviors in zirconium alloys with nanostructure and potential deformation texture.…”
mentioning
confidence: 90%
“…In experiments, although there are many reports about the torsional properties of materials, there are few results about irradiated materials, which can be summarized as the following: more hydrides are formed in high‐pressure torsion processed Zircaloy‐4 materials . Damage, crack growth, and fracture of nuclear grade graphite have been observed using a double torsion technique .…”
Section: Introductionmentioning
confidence: 99%